Presence of a High Amount of Stroma and Downregulation of SMAD4 Predict for Worse Survival for Stage I–II Colon Cancer Patients - Wilma E. Mesker; Gerrit-Jan Liefers; Jan M. C. Junggeburt; Gabi W. van Pelt; Paola Alberici; Peter J. K. Kuppen; Noel F. Miranda; Karin A. M. van Leeuwen; Hans Morreau; Karoly Szuhai; Rob A. E. M. Tollenaar; Hans J. Tanke (Cellular Oncology)
Background: For stage I–II colon cancer a significant number (5–25%) of patients has recurrent disease within 5 years. There is need to identify these high-risk patients as they might benefit from additional treatment.